2001
DOI: 10.1037/h0095082
|View full text |Cite
|
Sign up to set email alerts
|

Teaching in a new key: Effects of a co-taught seminar on medical students' attitudes toward schizophrenia.

Abstract: In order to examine the effect of a consumer and professional co-taught seminar on recovery in persons with schizophrenia, fourth year medical students completed attitudinal surveys at the beginning and end of their 7-week rotation in psychiatry. Analysis of results comparing average change in scores in a group exposed to the seminar (n = 24) and a control group not exposed (n = 10), shows measurable change in some survey items indicative of attitudinal change. Such a teaching format may provide a broader pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 9 publications
0
39
0
1
Order By: Relevance
“…It appears that the arguably obligatory contact health professionals have with consumers in the workplace may not be conducive to stigma reduction [5]. Although numerous studies have found significant success in specifically utilizing mental health consumers who have been trained to speak about their illness [32][33][34][35][36], the limited availability of these trained mental health consumers hinders their widespread implementation.…”
Section: Introductionmentioning
confidence: 99%
“…It appears that the arguably obligatory contact health professionals have with consumers in the workplace may not be conducive to stigma reduction [5]. Although numerous studies have found significant success in specifically utilizing mental health consumers who have been trained to speak about their illness [32][33][34][35][36], the limited availability of these trained mental health consumers hinders their widespread implementation.…”
Section: Introductionmentioning
confidence: 99%
“…In other studies with a similar design, investigators have shown improvement in the attitudes of medical students following a psychiatry rotation of six weeks or more (7,8,10). However some studies have not shown improvement of the stigma scores after a psychiatry clinical attachment especially when the duration of the clinical rotation is two weeks or less (9,11).…”
Section: Discussionmentioning
confidence: 99%
“…Positive educational experiences and positive personal experiences have been shown to improve attitudes (5)(6)(7)(8). Other research has shown that being exposed to persons with long term mental illness as well as being exposed to negative images of mentally ill people may worsen attitudes (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During undergraduate psychiatric training in particular, general attitudes to psychiatry are said to become more favourable (Coodin & Chisholm, 2001). However, in Australia, students also became more medically and 'authoritarian' oriented and less psychosocial and 'libertarian' oriented (Augustinos et ah, 1985).…”
Section: Studentsmentioning
confidence: 99%